2019
DOI: 10.3390/coatings9120846
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Surface Deterioration of Scrimber Composites Exposed to Artificial Ageing

Abstract: The effect of ultraviolet radiation on the surface deterioration of scrimber composites with different densities and levels of resin content was investigated for this paper. The surface color, gloss, roughness, and wettability of the samples were investigated to determine the extent of surface changes due to accelerated ageing. The results indicated that all scrimber composites exhibited variation in the color of their surfaces during artificial xenon light exposure. After artificial accelerated ageing, the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…When used outdoors, engineered wood composites are often affected by temperature, humidity, and biological agents. In particular, exposure to molds and decay fungi under appropriate humidity and temperature conditions can affect the color, morphology, and mechanical properties of timber [3][4][5]. White-and brown-rot fungi can degrade the polysaccharides and lignin in wood [6].…”
Section: Introductionmentioning
confidence: 99%
“…When used outdoors, engineered wood composites are often affected by temperature, humidity, and biological agents. In particular, exposure to molds and decay fungi under appropriate humidity and temperature conditions can affect the color, morphology, and mechanical properties of timber [3][4][5]. White-and brown-rot fungi can degrade the polysaccharides and lignin in wood [6].…”
Section: Introductionmentioning
confidence: 99%
“…Kataoka et al [ 8 ] reported that the spreading rate and extent of fungal degradation were dependent on the density of the composite. Furthermore, accelerated weathering is more likely to occur in low-density composites [ 9 ]. Previous studies have indicated that the dimensional stability and photostabilization of wood composites can be improved by increasing the concentration of phenol formaldehyde (PF) resin [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%